The Messiah of Ephraim and the Premature Exodus of the Tribe of Ephraim - Heinemann, Joseph (Harvard theological review, 1975)
A considerable number of detailed studies have been devoted to the Messiah of Ephraim (or of Joseph). Among the problems which were raised by scholars are the following: What need was there for the creation of another messianic figure? Why was this second Messiah ascribed to the Joseph tribes in particular? Why and when did the strange motif of the forerunner of the Davidic Messiah, who was doomed to fall in battle, come into being? Does this figure have any connection with the “suffering servant” of Isaiah or, perhaps, with the Christian Messiah, destined to suffer and die?